2020
DOI: 10.4314/agrosh.v19i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of ten pepper breeding lines to cucumber mosaic virus disease

Abstract: Pepper (Capsicum annuum) is a major vegetable of global importance. Its production is however affected by varying biotic and abiotic stresses. Virus infections possess a genuine danger to pepper cultivation in Nigeria and all over the world resulting in over 50 % yield losses. Thus, the need to subject available pepper germplasm to screening against virus diseases for possible identification of resistant genes which may be used in breeding programmes to obtain improved lines that are high yielding. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Through the use of a combination of amplified fragment length polymorphism (AFLP) marker, Bulk Segregant AnalysisBSA and allelism study, a new single recessive gene, cmr2 , capable of conferring resistance to resistance‐breaking CMV‐P1 isolate, was recently described (Choi et al, 2018). Today, infection with Cucumber mosaic virus (CMV)‐P1 in pepper production is a very serious issue, causing poor marketability of produce (Adama et al, 2020). Shin et al (2013) revealed that Korean domestic pepper cultivars on the market were susceptible to CMV‐P1, but 17.2% of foreign pepper cultivars and genetic pepper lines from RDA Genebank were resistant or partially resistant.…”
Section: Introductionmentioning
confidence: 99%
“…Through the use of a combination of amplified fragment length polymorphism (AFLP) marker, Bulk Segregant AnalysisBSA and allelism study, a new single recessive gene, cmr2 , capable of conferring resistance to resistance‐breaking CMV‐P1 isolate, was recently described (Choi et al, 2018). Today, infection with Cucumber mosaic virus (CMV)‐P1 in pepper production is a very serious issue, causing poor marketability of produce (Adama et al, 2020). Shin et al (2013) revealed that Korean domestic pepper cultivars on the market were susceptible to CMV‐P1, but 17.2% of foreign pepper cultivars and genetic pepper lines from RDA Genebank were resistant or partially resistant.…”
Section: Introductionmentioning
confidence: 99%